International orientation and business group performance: moderating role of product diversification (evidence from India). (2018) - Hota, Pradeep Kumar; Mitra, Sumit
Research on internationalisation and product diversification are primarily conducted at the firm level, leading to lack of understanding of these phenomena at the business group level. We address this gap by examining the effect of international orientation and product diversification on performance of business group and the moderating role of product diversification on international orientation and performance relationship. Using a sample of business groups from India, we tested our hypothesis by applying GLS fixed-effect regression model. Our result suggests that international orientation has a negative effect whereas product diversification has a positive effect on performance of business group. Further, presence of product diversification enhances the negative effect of international orientation on performance of business groups. Research findings have important implications for researchers as well as for business group managers.